Factors That Inhibit or Promote The Integration of ICT in Education - Quadros-Flores, Paula (2019)
The integration of digital technologies in education stimulates methodological changes with an impact on the ways of teaching to learn and learning to learn and, therefore, requires up-to-date digital resources available for innovative educational practices. In general, there have been projects that equipped Portuguese schools, but without concern for teacher training and, therefore, it is crucial to understand if the inclusion of these resources in the current educational environment promotes innovative practices or if there are still obstacles preventing change and the development of a student profile for the 21st Century [1]. The purpose of this study is to understand if the current reality still hinders change in education, or facilitates this change by making available a digital technological educational environment that supports innovative and dynamic practices that prepare students for the reality in which they live in. We also want to know if a classroom equipped for the frequent and effective use of ICT is enough and what makes teachers include digital technological resources in their educational practices. In this context, an exploratory quantitative and qualitative study was chosen. Data collection was carried out by open and closed questionnaire surveys. As for the analysis, in the first phase, three open questions were analyzed in 14 questionnaires applied to trainees in public elementary schools (1st cycle of basic education), and two open questions in five questionnaires applied to cooperating teachers, guiding these students to teach in the same schools. In the second phase, three closed questions were analyzed in a questionnaire applied to approximately 1200 teachers in the Porto metropolitan area. Trough the analysis of the results obtained in both phases mentioned above, four categories related to the obstacles that currently exist in primary schools and that negatively influence the teaching and learning process were identified. It was not surprising that the existence of digital technological resources in the educational context is not sufficient, since there are other factors that inhibit or promote the use of ICT. The obstacles which inhibit the frequency of use impose measures within the context of teacher training, including a reflection on the course syllabus. The factors that promote the use of ICT focus mainly on three categories. It was possible to verify that the success of the integration depends on: a) the articulation of aligned projects that involve the availability of various technological resources, namely computers and wireless networks; b) the context of the educational community; c) the training of children, the technical and pedagogical training of teachers and their creative capacity in the construction of strategies and didactic resources as well as their vision of education.